The Amazon Biome in Messages: Topic Explorer - Ruscica, Giosue; Carneiro, Bia (2025)
The "Amazon Biome in Messages: Topic Explorer" presents results from a multilingual topic modeling analysis of Telegram messages about the Amazon Biome. The dashboard is part of the research project The Amazon Biome in Messages, which aims to investigate how debates concerning the Amazon Biome are framed and disseminated within public Telegram channels in English, Portuguese, and Spanish.